2020
DOI: 10.1163/23641177-bja10012
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Competency in Competency-Focused Science Teaching in the South Korean Context: Teacher Self-Assessment Instrument Development and Application

Abstract: The purpose of this study was to examine teachers’ competency in teaching for student competence in science. Drawing on literature on competence and science teacher education, we identified 44 indicators of science teaching competence in relation to the current Korean National Science Curriculum, from which 54 items for teachers’ self-assessment were developed and validated. Through online administration of the self-assessment instrument, responses from 210 primary and secondary teachers were collected. Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…45 Therefore, teacher's competencies are identified as the most effective contribution to support student achievement, 46 which is essential for teacher education and professional development. 47 Thus, through CIPS training, teachers can plan the learning that they will undertake in the classroom, conduct learning that provides the most significant opportunity for learners to explore the abilities and skills that exist in them, as well as to conduct evaluations that not only focus on one aspect of cognitive but also evaluate the affective and psychomotor aspects of learners. 48 Subsequently, problem-solving for each teacher also improved as they went through the CIPS-based Training Module.…”
Section: Figure 1 Difference Between Experiments Group and Control Groupmentioning
confidence: 99%
“…45 Therefore, teacher's competencies are identified as the most effective contribution to support student achievement, 46 which is essential for teacher education and professional development. 47 Thus, through CIPS training, teachers can plan the learning that they will undertake in the classroom, conduct learning that provides the most significant opportunity for learners to explore the abilities and skills that exist in them, as well as to conduct evaluations that not only focus on one aspect of cognitive but also evaluate the affective and psychomotor aspects of learners. 48 Subsequently, problem-solving for each teacher also improved as they went through the CIPS-based Training Module.…”
Section: Figure 1 Difference Between Experiments Group and Control Groupmentioning
confidence: 99%
“…Teachers should develop their teaching competencies with cultural sensitivity. Teaching competency indicates what teachers should know and be able to do to teach effectively (Danielson, 2007;Kang et al, 2020;Vogt & Rogalla, 2009). For example, Kang et al (2020) identified 44 indicators of teaching competency in the context of science teaching.…”
Section: 3mentioning
confidence: 99%
“…Teaching competency indicates what teachers should know and be able to do to teach effectively (Danielson, 2007;Kang et al, 2020;Vogt & Rogalla, 2009). For example, Kang et al (2020) identified 44 indicators of teaching competency in the context of science teaching. Such indicators can be applied to culturally responsive teaching.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Danielson's (2007) 'teaching framework' consisting of 22 components in four domains, one of the domains is 'planning and preparation' (the other three domains are 'the classroom environment' , 'instruction' and 'professional responsibilities'), which includes 'designing coherent instruction' component. In the self-assessment instrument for science teacher competency developed by Kang et al (2020), 17 elements among total 54 elements were included in a category of 'Science Lesson Preparation Competency' . Jacobs et al (2008) have developed a 'Science Lesson Plan Analysis Instrument' consisting of 21 items, including 'goal orientation' , 'students' participation' , 'appropriate use of technology' , and so on.…”
Section: Introductionmentioning
confidence: 99%